About the Little-Known Pages of the Biography of Tseren-Dordzhi Nominkhanov: the period of formation, military activity and studies at the Institute (1918th–1930s) - Elza P. Bakaeva; Sanan A. Nominkhanov (Монголоведение)
Introduction. The article is devoted to the personality of a prominent orientalist, the first doctor of Philology of Kalmykia, Tseren-Dordzhi Nominkhanov. The purpose of the article is to analyze and introduce into scientific circulation little-known and previously unknown data on the biography of Tseren-Dordzhi Nominkhanov from the first years of his activity (before 1930th). The materials for the study were both individual documents and data from surveys conducted in different years in Kalmykia. The information obtained as a result of the interviews provides an opportunity to expand the understanding of the difficult life path of the scientist and the fate of his people, testifies to the relevance of using an integrated approach in biographical research. Results. To date, there are different spellings of the scientist's name in the scientific literature, which is due to his use of both variants in the early and late periods of his activity, as well as the peculiarities of the Kalmyk onomasticon. The authors pay attention to the environment in which the formation of Ts.-D. Nominkhanov took place, and a possible influence on the subsequent formation of the researcher. The data of surveys containing new information about the life of Ts.-D. Nominkhanov, as well as data from archival materials, testifying to the difficult initial path of becoming a scientist, are presented.